Production of Highly Efficient Pt/C for PEM Fuel Cell Applications - Ozdemir, Julide Hazal; Hasimoglu, Aydin; Elcicek, Huseyin; Ozdemir, Oguz Kaan; Akkas, Nuri (Springer, 2025)
PEM fuel cell technologies have emerged as promising candidates for advancing sustainable energy solutions, primarily due to their exceptional efficiency and minimal environmental impact. However, the widespread commercialization of fuel cells is hindered by the high cost and limited availability of platinum catalysts, which play a critical role in facilitating electrochemical reactions. This research mainly focused on investigating innovative solutions aiming to mitigate platinum loading while simultaneously preserving or potentially enhancing their performance. To this end, the impact of two distinct surfactants, Tween 40 and Tween 80, was examined to assess their influence on the synthesis and characteristics of platinum nanoparticles immobilized on carbon supports. Subsequently, their electrochemical activities were compared. The catalysts were synthesized using the polyol method with the incorporation of surfactants, and their performance was compared with that of Pt/C catalysts without surfactants. TGA analysis indicated a significant reduction of approximately 12% in the Pt content of the catalyst synthesized using Tween 80 surfactant. However, CV analysis revealed a remarkable increase of 85% in the ECSA for the same catalyst. Furthermore, significant improvements in the performance of this catalyst were also observed in the single-cell test setup. The high performance achieved with a lower Pt content in the catalyst layer highlights its potential for large-scale commercialization.
Keywords: Sustainability; PEM fuel cell; Catalysts; Oxygen reduction reaction; Tween 80